The effect of wheat straw treated with different chemicals on ruminal fermentation in angora goats - Çakmak, Cemal; Halil Çerçi, I. (Scientific and Technical Research Council of Turkey, 1996)
In this trial, the effects of wheat straws-which is commonly used for feeding ruminants both as roughage and balast matter source-treated with different concentrations HCl (20%, 30% HCl). (S+20-HCl, S+30-HCl) HCl (20%. 30% HCl) + Urea (S+20-HCl+Ü. S+30-HCl+Ü) and Urea (4%) (S+Ü) using ruminal cannules fitted four Angora Goat Bucks on ruminal fermentation were investigated. The avarage pH values of ruminal liquid were found the highest in group S and the lovest in group S+20-HCl+U (p<0.05). In the buffer capacity similer situation was observed. The NH3-N values were determined to be increasing generally in the urea treated groups, the highest value was determined in group S+20-HCl+U (p<0.05), and results were found to be significant (p<0.001). The volatile fatty acid levels at two hours after feeding were determined high in all groups compare to before feeding (p<0.05). The amounts of total-N of ruminal liqued and bacterial-N and DAPA-N in bakterial sediment (%/Dm)were found to be higher in the urea treated groups than non urea groups. The DAPA (mg/gDM) concentration of bacterial sediment was found higher in non urea group than other groups.
Ankara Keçilerinde Farkli Kimyasal Maddelerle Işlenen Bu?day Samaninin Ruminal Fermentasyona Etkisi
Keywords: Chemical treatment; Diaminopimelic acid; Ruminal fermentation; Straw